Control of HIV infection: Escape from the shadow of Blimp‐1. Issue 2 (14th February 2013) - Thaventhiran, James E.; Fearon, Douglas T.
<x xml:space="preserve">Abstract</x> Prior murine studies have demonstrated the pivotal role that Blimp‐1 has in the exhausted phenotype of T lymphocytes in chronic viral infection. In this issue of the European Journal of Immunology, Seddiki et al. [Eur. J. Immunol. 2013. 43: 510–520] demonstrate the applicability of this research to HIV infection. The authors do so by demonstrating differences in Blimp‐1 expression between T lymphocytes isolated from patients with chronic active HIV versus those from long‐term nonprogressors and showing that this is matched by differences in the cells' capacity to produce IL‐2 and the level of expression of the inhibitory receptor PD‐1. The data presented here suggest that this may relate to differential regulation of Blimp‐1 by the micro RNA, mIR‐9. These findings complement current murine work and fit squarely within the research priorities, as outlined by the International AIDS Society, for determining a cure for AIDS.